A randomised controlled trial of a community intervention to prevent adolescent tobacco use. Issue 1 (1st March 2000) - Biglan, Anthony; Ary, Dennis V; Smolkowski, Keith; Duncan, Terry; Black, Carol
Abstract : OBJECTIVE: Experimental evaluation of comprehensive community wide programme to prevent adolescent tobacco use. DESIGN: Eight pairs of small Oregon communities (population 1700 to 13 500) were randomly assigned to receive a school based prevention programme or the school based programme plus a community programme. Effects were assessed through five annual surveys (time 1–5) of seventh and ninth grade (ages 12–15 years) students. INTERVENTION: The community programme included: (a) media advocacy, (b) youth anti-tobacco activities, (c) family communications about tobacco use, and (d) reduction of youth access to tobacco. MAIN OUTCOME MEASURE: The prevalence of self reported smoking and smokeless tobacco use in the week before assessment. RESULTS: The community programme had significant effects on the prevalence of weekly cigarette use at times 2 and 5 and the effect approached significance at time 4. An effect on the slope of prevalence across time points was evident only when time 2 data points were eliminated from the analysis. The intervention affected the prevalence of smokeless tobacco among grade 9 boys at time 2. There were also significant effects on the slope of alcohol use among ninth graders and the quadratic slope of marijuana for all students. CONCLUSION: The results suggest that comprehensive community wide interventions can improve on the preventive effect of school based tobacco prevention programmes and that effective tobacco prevention may prevent other substance use.